Co-localization of P2Y1 receptor and NTPDase1/CD39 within caveolae in human placenta - A Kittel; Zs CsapÃ³; E Csizmadia; SW Jackson; SC Robson (European Journal of Histochemistry, 2009)
Nucleoside triphosphate diphosphohydrolase-1 (NTPDase1/ CD39) is the dominant ecto-nucleotidase of vascular and placental trophoblastic tissues and appears to modulate the functional expression of type-2 purinergic (P2) Gprotein coupled receptors (GPCRs). Hence, this ectoenzyme could regulate nucleotide-mediated signalling events in placental tissue. This immunohistochemical and immuno-electron microscopic study demonstrates the expression of NTPDase1/CD39, P2Y1 and P2Y2 receptors in different cell types of human placenta. Specifically P2Y1 has an exclusive vascular distribution whereas P2Y2 is localized on trophoblastic villi. Co-localization of P2Y1 and NTPDase1/ CD39 are observed in caveolae, membrane microdomains of endothelial cells. The differential localization of these P2 receptors might indicate their unique roles in the regulation of extracellular nucleotide concentrations in human placental tissues and consequent effects on vascular tone and blood fluidity.